Association between physical activity levels and symptoms of depression and anxiety among Human Medicine students - Arrascue, Joaquín (2023)
Objective: To evaluate the association between levels of physical activity and depression and anxiety symptoms among medical students. Methods: Observational cross-sectional study that used 3 questionnaires: the Patient Health Questionnaire (PHQ-9) to assess depression symptoms, the Generalized Anxiety Disorder scale (GAD-7), and the International Physical Activity Questionnaire, short version (IPAQ). Results: 146 students participated in the study. The higher the level of physical activity, the lower were the scores on the depression and anxiety scales; however, no significant differences were found in the median scores of the PHQ-9 (p = 0.121) and GAD-7 (p = 0.393) between the three levels of physical activity. It was found that women and students in the first three years of study had higher scores on the PHQ-9 and GAD-7 scales. Conclusions: There was a non-significant tendency for medical students with greater physical activity to have lower scores on the depression and anxiety measurement scales.